HAEMATOLOGICAL PARAMETERS ALTERED IN TUBERCULOSIS - Iqbal, Sumaira; Ahmed, Umbreen; Khan, Muhammad Alamgir (Pakistan Journal of Physiology, 2015)
Tuberculosis is a chronic granulomatous inflammation highly prevalent in developing countries resulting in high mortality rate. The study was conducted to investigate the change in haematological parameters with effective anti-tuberculosis therapy. Methods: A total of 45 active tuberculous patients and 45 age and sex matched healthy controls were enrolled for study by convenient non-probability sampling. Patients were taken from Military Hospital, Rawalpindi, whereas controls were taken from community. All the subjects underwent blood sampling for complete blood picture. The samples were taken in ethylene diamine tetraacetic acid (EDTA) treated tube and were analysed in KX-21 SysmexÂ® automated haematology analyser. Differential leukocyte count was done manually by microscopy of Leishmanâ€™s stained blood films. Statistical analysis was done and p<0.05 was considered significant. Results: Haemoglobin and lymphocyte were significantly different in cases and controls at time of diagnosis. Haemoglobin concentration, neutrophil, monocyte and lymphocyte count were significantly different, whereas total leukocyte counts were not significantly different. Change in platelet count among cases and controls were statistically significant. Monocyte Lymphocyte (M/L) ratio and Lymphocyte Neutrophil (L/N) ratio were also significantly different. Conclusion: Haemoglobin concentration, platelet count, lymphocyte count, and neutrophil count alter with chronic inflammatory process and revert to normal with effective therapy. These parameters can be used as indicators in the assessment of response to chemotherapy.